Gender Representation in EFL Coursebook Used for Islamic Elementary School of Bengkulu: A Content Analysis - Hayadi, Algrin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The goal of this study is to identify the bias of gender in the coursebooks. So, the representation of males and females in the coursebook will be analyzed in this research. This study focuses on Gender Representation in EFL coursebook used in Islamic elementary school in Bengkulu city. The object of this research is the Coursebook entitled “Grow With English 4” (A Thematic English Coursebook for elementary Students published by Erlangga, Jakarta, 2017). This study is a qualitative study that uses content analysis as the method of research to describe the content of the coursebook. The content analysis in this research will focus on six aspects based on Logsdon. They are; number of male/female pictures, number of male/female mentioned, number of male/female roles, number of male/female games, number of male/female roles models, and pattern of mentioning male/female names. The results of the study showed that gender represented unequally in the grow with English 4. males are more visible in five aspects including pictures, male/female mentioned, gender roles, female,male games, and gender role models. However there are some weaknessess that found in the course book needed to be improved so that the objective of the learning will be achieve by students maximally.